Employee Competencies for Tourism Object Destination Management in the Destination Field of the Tourism and Culture Office of Pangandaran District - Davka Avicenna, Muhamad (Decision, 2022)
This research has a background regarding employee competency for managing tourism object destinations in the tourism and culture department of Pangandaran Regency. The author is interested in researching this problem because he wants to know more about employee competency for managing tourism object destinations in the District Tourism and Culture Department's Destination Sector. Pangandaran. Based on the results of observations in the field, there are several problems, namely regarding Knowledge, Understanding, Ability/Skills, Values, Attitudes and Interests. The theory used in this research is the theory according to Gordon in Sutrisno (2011: 204) The objectives of this research are 1) To determine employee competence for managing tourism destinations in the tourism and culture department of Pangandaran Regency 2) To determine the dimensions which was analyzed regarding employee competency for managing tourism destinations in the tourism and culture department of Pangandaran Regency. With this research, the author used a qualitative approach and descriptive method, data collection techniques using interview techniques, which were carried out with the head of the Head of General and Civil Service Sub-department, the Head of Sub-Destination UPT Pangandaran Region and the Sub-General and Personnel Apparatus of the tourism and culture office of Pangadaran Regency, observations and documentation. The data obtained in this research was processed using qualitative procedures according to Miles & Huberman (1992:16) including analytical techniques for data reduction, data presentation, and drawing conclusions. The conclusion of this research is that employee competence for managing tourism destinations is still not fully operational and is still less than optimal in its management, considering that the resources of service personnel are still lacking and there are still deficiencies in the use of information technology in managing tourism objects. The researcher's suggestions for the Pangandaran Regency Tourism and Culture Office in managing tourism destinations in Pangandaran Regency should be to be more active and develop further in increasing employee competency in managing tourism destinations so that improvements related to tourism objects can run well and be more advanced in management carried out by service employees to be able to improve various management promotions using media, internet and social media in processes related to employee competency for managing tourism destination objects in Pangandaran Regency.